CASES OF DENTAL FLUOROSIS IN THE KEMEROVO REGION - Ирина Владимировна Куприна; Елена Александровна Киселева; Игорь Анатольевич Те; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
Concentration of the ionised fluorine in mineral water «Borisovsky» makes 7,392±0,013 mg/l and the dosed out application of mineral water «Borisovsky» can serve as an effective and cheap method of preventive maintenance of caries of a teeth in territories with the low maintenance of fluorine in potable water.